Being Indian : the truth about why the twenty-first century will be India's - Varma, Pavan K. (New Delhi ; New York, NY : Viking, 2004)
On the changing perspectives in social life of East Indians and their attitudes; reflecting on the socio-political mileau in India.
Keywords: East Indians -- Attitudes; India -- Social life and customs -- 21st century; India -- Politics and government -- 1977-